CALISTUNG TRAINING AND ENGLISH VOCABULARY IMPROVEMENT FOR SCHOOL CHILDREN IN SUKAJULU VILLAGE - Januaris Pane; Dewi Lestari Pardede; Irawati Br Munthe; Esra Yohana Sirait; Juniarta Butar Butar; Putri Ayu Panggabean; Theo Clinton Siallagan (PKM Maju UDA, 2022)
Community Service activities carried out by students do not mean teaching the community about what is best for them, but carrying out empowerment as a process of searching (research) carried out together to find the best way to solve the problems they face. Students carry out the task of assisting what is needed by the community in dealing with social problems that exist in their midst. This method is considered to play an important role because of a number of benefits. In children, reading can be seen as simply sounding strings of letters or letters, writing means writing letters together, and counting means simply adding, multiplying, and dividing.